Epidemiological characteristics of two COVID-19 outbreaks caused by SARS-CoV-2 prototype and Omicron variant in border area of Yunnan province: a comparative analysis - Yu-bing QIU; Man-hong JIA; Jin-ou CHENG (Editorial Office of Chinese Journal of Public Health, 2022)
ObjectiveTo examine the difference in epidemiological characteristics of coronavirus disease 2019 (COVID-19) epidemics caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) prototype strain and Omicron variant in a border area of Yunnan province for providing references to real-time adjustment of regional measures on COVID-19 epidemic prevention and control. Methods Field surveys were conducted to collected relevant information on confirmed cases, asymptomatic infections, close contacts and secondary close contacts from two COVID-19 outbreaks in Ruili - a border city of Yunnan province: an epidemic during March 29 - April 19, 2021 caused by SARS-CoV-2 prototype strain based on whole gene sequencing (abbreviated as prototype-caused epidemic) and an another during February 16 - March 26, 2022 caused by SARS-CoV-2 Omicron variant BA.2 (variant-caused epidemic). Descriptive statistics were performed to compare epidemiological characteristics between the two COVID-19 outbreaks. ResultsBoth the two outbreaks were induced by imported cases from abroad. The majority of sufferers were confirmed cases (93/117, 79.49%) for the prototype-caused epidemic and were asymptomatic infections (314/384, 81.77%) for the variant-caused epidemic, with a significant difference in the proportion between the two epidemics (χ2 = 177.254, P < 0.001). In nucleic acid tests at the time of diagnosis, the cycle threshold (Ct) values of ORF1ab gene and N gene for the cases infected with SARS-CoV-2 prototype strain were significantly higher than those for the cases with SARS-CoV-2 Omicron variant infection (Z = 6.089, 6.924, P < 0.001). The proportions of cases aged < 15 years and > 60 years in the variant-caused epidemic were significantly higher than those in the prototype-caused epidemic (χ2 = 33.236, P < 0.001). The incubation period (median [M], 25th percentile [P25], 75th percentile [P75]) for the secondary infections among close contacts was not significantly different between the two epidemics (3 [1,4.75] vs. 3 [2, 5], Z = - 1.54, P = 0.124), with 88.75% and 95.24% of the secondary infections having the incubation period less than 7 days for the prototype- and variant-caused epidemic. The secondary infection rate of close contacts was 1.17% (80/6 833) and 2.78% (145/5 223) and the rate of core close contact was 6.3% (58/920) and 6.23% (111/1782) for the prototype- and variant-caused epidemic. No secondary infection was detected among general close contacts and secondary close contacts and the secondary infection rate was the highest among the contacts living together with confirmed cases, followed by that among those having dinner with the confirmed cases. Totally 11 and 48 clustering epidemics were identified in the two COVID-19 outbreaks caused by SARS-CoV-2 prototype strain and Omicron variant, involving 76.07% and 33.85% of all diagnosed cases during the two outbreaks. ConclusionCompared to SARS-CoV-2 prototype strain, SARS-CoV-2 Omicron variant BA.2 exhibits higher infectivity and could result in more asymptomatic infections. The study results should be considered in developing measures on COVID-19 epidemic prevention and control.